PKM Pengelolaan Koperasi Sekolah Melalui Sistem Berbasis Syariah Di Yayasan An-Nahlu Kecamatan Kisaran Timur Kabupaten Asahan Sumatera Utara - Muhammad Zuardi; Kholil , Ahmad; Supaino; Cahyoginarti; Sudarsono (LPPM ITEBA, 2025)
The foundation is currently supporting the establishment of a cooperative within the school, which could help provide snacks for teachers and the surrounding community. However, it feels necessary to increase knowledge about Sharia principles, given that the foundation is an Islamic educational institution. The community in this institution needs to be given an understanding about managing the potential of business units and developing an entrepreneurial spirit so that in the future they can manage it well. This activity began with a preparatory phase that included a site review at the An-Nahlu Foundation in Kisaran Timur, Asahan, North Sumatra, a field study for problem analysis and solutions, and proposal preparation and permit administration. After the preparations were completed, the implementation activities were carried out at the An-Nahlu Foundation with 20 participants, including educators, education staff, and foundation administrators. The materials provided included an explanation of sharia-based cooperatives, sharia contracts, and motivations for developing cooperatives as a vehicle for collecting and distributing funds for teachers. From the training with the aim of making community groups aware and motivated about the importance of cooperatives and from the activities that have been carried out, it is known that 70% of participants really understand this, so they have a strong desire to establish a cooperative forum, in its implementation this cooperative awareness really wants to be followed up by providing assistance in making cooperative permits by starting with the desire to register participants who want to become founders of the cooperative, the output measure of this activity is with an indicator that 70% of training participants understand well about the importance of cooperatives that can be achieved well.